Step-by-step explanation:
Give the first 8 terms of the sequence. a1= -1, a2=2, a[n]=a[n-2](3-a[n-1])
Given
first term a1 = -2
second term a2 = 2
We are to get the first 8 terms. Given the sequence
a[n]=a[n-2](3-a[n-1])
a[3]=a[3-2](3-a[3-1])
a[3]=a[1](3-a[2])
a[3]=-2(3-2)
a3 = -2
a[n]=a[n-2](3-a[n-1])
a[4]=a[4-2](3-a[4-1])
a[4]=a[2](3-a[3])
a[4]=2(3+2)
a4= 10
a[5]=a[n-2](3-a[n-1])
a[5]=a[5-2](3-a[5-1])
a[5]=a[3](3-a[4])
a[5]=-3(3-10)
a5 = -3(-7)
a5 = 21
a[6]=a[n-2](3-a[n-1])
a[6]=a[6-2](3-a[6-1])
a[6]=a[4](3-a[5])
a[6]= 10(3-21)
a6 = 10(-18)
a6 = -180
a[n]=a[n-2](3-a[n-1])
a[7]=a[7-2](3-a[7-1])
a[7]=a[5](3-a[6])
a[7]= 21(3+180)
a7 = 21(183)
a7 = 3,843
a[8]=a[n-2](3-a[n-1])
a[8]=a[8-2](3-a[8-1])
a[8]=a[6](3-a[7])
a[8]=-180(3-3843)
a8 = -180(-3840)
a8 = 691,200